2014
DOI: 10.5089/9781484393741.001
|View full text |Cite
|
Sign up to set email alerts
|

Financial Constraints, Intangible Assets, and Firm Dynamics: Theory and Evidence

Abstract: I study whether firms' reliance on intangible assets is an important determinant of financing constraints. I construct new measures of firm-level physical and intangible assets using accounting information on U.S. public firms. I find that firms with a higher share of intangible assets in total assets start smaller, grow faster, and have higher Tobin's q. Asset tangibility predicts firm dynamics and Tobin's q up to 30 years but has diminishing predicative power. I develop a model of endogenous financial constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…12 Similarly, z structure j;t is computed as a weighted average of the present value of depreciation allowances across all structural assets. 9 Several recent studies use firm-level R&D or selling, general, and administrative (SG&A) expenses to measure intangible assets (Eisfeldt and Papanikolaou 2013;Falato, Kadyrzhanova, and Sim 2013;Chen 2014); however, SG&A does not have a breakdown of investment by asset types. 10 For the book value of physical assets, we experiment with different measurements used in the literature and choose to present results based on the book value of plant, property, and equipment.…”
Section: Methodology Empirical Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Similarly, z structure j;t is computed as a weighted average of the present value of depreciation allowances across all structural assets. 9 Several recent studies use firm-level R&D or selling, general, and administrative (SG&A) expenses to measure intangible assets (Eisfeldt and Papanikolaou 2013;Falato, Kadyrzhanova, and Sim 2013;Chen 2014); however, SG&A does not have a breakdown of investment by asset types. 10 For the book value of physical assets, we experiment with different measurements used in the literature and choose to present results based on the book value of plant, property, and equipment.…”
Section: Methodology Empirical Specificationsmentioning
confidence: 99%
“… An alternative to Corrado, Hulten, and Sichel's (2005) method is to use R&D or selling, general, and administrative (SG&A) expenses (Eisfeldt and Papanikolaou ; Falato, Kadyrzhanova, and Sim ; Chen ). Corrado, Hulten, and Sichel's (2005) method is preferable because it allows us to correctly measure the benefit of tax incentives by asset type.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We use domestic credit as a percentage of GDP (World Bank) to measure financial development and the availability of credit, while the contract enforcement index (World Bank, Doing Business) to proxy for the ability of the legal system to enforce contracts and resolve disputes.56 See, for instance,Chen (2014). Furthermore, notice that, as expected, the overall marginal effect of both credit market development and contract enforceability on firms' productivity is significantly positive when all covariates are fixed at their means.…”
mentioning
confidence: 99%
“…At the firm level, several studies capitalize reported R&D or Sale, General, and Administrative (SG&A) expenses to construct intangible assets(Chen 2014, Eisfeldt and Papanikolaou 2013, Falato, Kadyrzhanova, and Sim 2013. However, SG&A does not have a breakdown of investment by asset types.…”
mentioning
confidence: 99%